1998
DOI: 10.1161/01.str.29.11.2412
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Doppler Scanning of Local Cerebral Blood Flow and Reserve Capacity and Testing of Motor and Memory Functions in a Chronic 2-Vessel Occlusion Model in Rats

Abstract: Background and Purpose-An animal model of incomplete forebrain ischemia resembling human hemodynamic insufficiency was established. The model allows examination of acute and chronic changes of local cerebral blood flow (lCBF) and reserve capacity in correlation with behavioral parameters. Methods-Anesthetized male Wistar-Kyoto rats underwent bilateral carotid occlusion (BCO). Laser-Doppler scanning of lCBF at baseline conditions and after acetazolamide was done 30 minutes after BCO, motor and memory function t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…reserve capacity. Impaired response to acetazolamide has been observed immediately postocclusion in WKY rats with common carotid artery occlusion and this persisted for 4 wk (50).…”
Section: Discussionmentioning
confidence: 96%
“…reserve capacity. Impaired response to acetazolamide has been observed immediately postocclusion in WKY rats with common carotid artery occlusion and this persisted for 4 wk (50).…”
Section: Discussionmentioning
confidence: 96%
“…Ischemia-induced neuronal degeneration is also observed in other structures, such as the striatum, cerebral cortex and thalamus (7)(8)(9). In this model, there is an abrupt reduction of whole brain blood flow, ranging from approximately 35-45% in the cortical area to 60% in the hippocampus compared to control levels (4,(10)(11)(12). This hypoperfusion is believed to sustain a chronic state of moderate hypoglycemia, a pathophysiological condition closely resembling that of reduced cerebral blood flow present in human aging and dementia (6).…”
mentioning
confidence: 83%
“…Among the animal models of chronic cerebral hypoperfusion, permanent 2-VO has been widely used but has a high mortality rate and reduced blood flow to both cerebral hemispheres suddenly, which does not match the situations in patients (7)(8)(9). A study performed on adult C57BL/ 6J mice with permanent RCCAO showed that 1-VO induced non-spatial memory deficits detected by objective recognition test, but these mice did not have spatial memory deficits detected by T maze spontaneous alternation test.…”
Section: Discussionmentioning
confidence: 99%
“…The most widely used experimental model is permanent bilateral common carotid arteries occlusion (two-vessel occlusion, 2-VO) in rodents (7). Permanent 2-VO produces a sudden decrease of cerebral blood flow to both cerebral hemispheres by 30% to 40% of the control level (8), which does not simulate the gradual decline of the ce-…”
mentioning
confidence: 99%